1985
DOI: 10.1111/j.1365-2141.1985.tb07358.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete correction of Glanzmann's thrombasthenia by allogeneic bone‐marrow transplantation

Abstract: Allogeneic bone marrow transplantation (BMT) successfully corrected type I thrombasthenia in a 4-year-old boy. The donor was his HLA-A, B and D identical 14-year-old brother who was heterozygous for thrombasthenia. A first transplant after conditioning with cyclophosphamide and thoracoabdominal irradiation was rejected, but a second transplant using CCNU, cyclophosphamide, procarbazine and horse antihuman thymocyte globulin in the preparative regimen was successful. Engraftment was proven by studies of platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…6 Type 1 GT was confirmed because platelet aggregation and clot retraction were repeatedly nil, and GPIIb/IIIa complex undetectable either by SDS-PAGE electrophoresis, immunoblotting or flow cytometry. 9 She had frequent epistaxis leading to severe anemia requiring continuous iron supplementation.…”
Section: Casementioning
confidence: 98%
See 2 more Smart Citations
“…6 Type 1 GT was confirmed because platelet aggregation and clot retraction were repeatedly nil, and GPIIb/IIIa complex undetectable either by SDS-PAGE electrophoresis, immunoblotting or flow cytometry. 9 She had frequent epistaxis leading to severe anemia requiring continuous iron supplementation.…”
Section: Casementioning
confidence: 98%
“…6 He was diagnosed as having type I thrombasthenia at the age of 2 years. At the age of 4, he had repeated life-threatening hemorrhages which required several transfusions.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow transplantation and stem cell reconstitution can cure the disorder, 234,235 but the risks of these procedures remain substantial, even with newer conditioning regimens, and thus they are still not desirable options for most patients (reviewed in Flood et al 236 ). Proof of concept for gene therapy of Glanzmann thrombasthenia has been provided in animal models 237 (reviewed in Wilcox and White 238 ), but much more remains to be done, including how to deal with the immune response to the newly expressed ␣IIb␤3.…”
Section: Org Frommentioning
confidence: 99%
“…Although Caen 17 stressed the amelioration of bleeding manifestations with age, Reichert et al 5 have confirmed that bleeding manifestations persist into adulthood. Some patients benefit from allogenic bone marrow transplantation, 18 but in many platelet transfusion therapy controls the bleeding or epistaxis. …”
Section: Discussionmentioning
confidence: 99%